Accidental and Nonaccidental Head Injuries in Infants: Distinguishing Characteristics - J Gordon Millichap (Pediatric Neurology Briefs)
One hundred fifty infants hospitalized with head injury over a 3-year period, 57 (38%) due to child abuse, were studied prospectively at the Departments of Pediatric Neurosurgery, Neuro-ophthalmology, and Legal Medicine, CHRU de Lille, France.